A dataset of plant communities invaded by Acacia sp. pl. and Robinia pseudoacacia in Italy - Eugenia Siccardi; Alice Misuri; Alicia Teresa Rosario Acosta; Claudia Angiolini; Dario Azzaro; Gianluigi Bacchetta; Simonetta Bagella; Elena Barni; Giuseppe Bazan; Maria E. Boi; Gianmaria Bonari; Giuseppe Brundu; et al. (Plant Biosystems, 2026)
The full extent of the ecological threat posed by non-native invasive leguminous N-fixing trees to Italian ecosystems has not been thoroughly documented at the national level. This study, conducted by the Working Group on Alien Species of the Italian Botanical Society, aims to develop a comprehensive dataset that provides information on invaded and non-invaded areas, supporting multi-scale ecological analyses on the impact of black locust ( Robinia pseudoacacia ) and different Acacia sensu lato species across Italy. We conducted paired vegetation surveys across 18 distinct invasion contexts, comparing invaded and non-invaded plant communities. These invasion contexts were selected opportunistically by the participating research groups, based on the availability of well-documented sites where the focal species were already established and exerting ecologically relevant effects. Overall, we conducted 342 vegetation surveys across 10 Italian administrative regions and identified 824 plant species. Our surveys highlighted areas affected by five invasive species, including A. dealbata, A. mearnsii, A. saligna , Vachellia karroo , and R. pseudoacacia . Most of the surveys focused on areas invaded by A. saligna . The plant formations investigated fall under 23 EUNIS habitat codes and 10 Natura 2000 habitats. The most frequently occurring vegetation types under the EUNIS code are temperate and Mediterranean-montane scrub, and the most frequently investigated habitat is priority habitat 2250*: Coastal dunes with Juniperus sp. pl. This dataset provides a robust baseline that can facilitate more detailed assessments of the impacts of these invasive species on native ecosystems.